ETHNOPHARMACOLOGICAL AND NUTRITIONAL EVALUATION OF WILD EDIBLE PLANTS IN KORAPUT DISTRICT, ODISHA - SAMEER JENA; IPSITA PRIYADARSINI SAMAL; PRATYASHA MOHANTY; SUDHANSU SEKHAR DASH; RAM BABU; GYANRANJAN MAHALIK (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: This ethnopharmacological study comprehensively assessed the nutritional and bioactive qualities of wild edible plants in the tribal habitat of Koraput, Odisha, India, to evaluate their potential in addressing micronutrient deficiencies and supporting food security in underserved rural populations. Methods: Through systematic collaboration with indigenous knowledge holders, we examined 25 wild plant species from diverse taxonomic categories using standardized analytical techniques. Nutritional profiling included proximate composition analysis, mineral content determination, vitamin quantification, and anti-nutritional factor assessment. Antioxidant potential was evaluated using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assays. Seasonal availability mapping was conducted to understand resource accessibility patterns. Results: Quantitative analyses revealed superior nutritional profiles compared to conventionally cultivated vegetables. Emblica officinalis demonstrated exceptional Vitamin C content (478.56 mg/100 g), Amaranthus spinosus exhibited remarkable iron levels (28.7 mg/100 g), and wild fungus Termitomyces spp. showed superior protein composition (32.4 g/100 g). DPPH radical scavenging assays indicated significant antioxidant potential, with capacities ranging from 38.6% to 87.3% (p<0.05). Comprehensive mineral profiling revealed substantial concentrations of essential micronutrients, including calcium, iron, and zinc. Vitamin analysis confirmed robust water-soluble and fat-soluble vitamin reservoirs across species. Anti-nutritional factor measurements provided insights into nutrient bioavailability and absorption efficiency. Conclusion: This study establishes the critical importance of wild edible resources in tribal food security, particularly during pre-monsoon resource-scarce periods. The findings bridge traditional ecological knowledge with modern nutritional science, providing a robust framework for addressing micronutrient deficiencies while supporting Sustainable Development Goals 2 (Zero Hunger) and 15 (Life on Land). The documented nutrient-dense wild food sources offer sustainable solutions for ecosystem management and preservation of endangered indigenous ecological knowledge threatened by rapid socioeconomic changes.